Effects of Different Preparation Techniques on Mechanical Property and Electrical Conductivity of Cu-8wt% Ag Alloy by Continuous Casting. Issue 8 (August 2016) - Yue, Shen; Ming, Xie; Jun, Bi; Guoquan, Zhang; Weiming, Guan; Ming, Wen; Song, Wang
Abstract: Cu-8wt%Ag alloy was prepared by two kinds of preparation techniques, namely continuous casting + cold wire-drawing deformation preparation (CC + CD) and continuous casting + equal channel angular pressing + cold wire-drawing deformation preparation (CC + ECAP + CD), and subsequently the aging treatment was performed. We measured the mechanical property and the electrical property of the Cu-8wt%Ag alloy with different strains, explored the changing rules of the microstructure, the mechanical property and the electrical property by different preparation techniques. Then we analyzed the changing reasons of performance and discussed whether the better comprehensive performance could be acquired by combining the ECAP with the traditional cold-processing. The results show that the comprehensive performance of the Cu-8wt%Ag alloy prepared by CC + ECAP + CD is a little better than that by CC + CD. It is significant and valuable to solve the waxing and waning problem between the high strength and high conductivity of the Cu-Ag alloy.